TINJAUAN TENTANG PERAN DAN FUNGSI LEMBAGA-LEMBAGA NEGARA DI INDONESIA - Subhan Sofhian (Tatar Pasundan: Jurnal Diklat Keagamaan, 2018)
Indonesia is a country that is still developing with principles on the four pillars of nationality, namely Pancasilan, the 1945 Constitution, Bhineka Tungga Ika and the Republic of Indonesia. In executing the government by using a presidential system, the president's duty is not only as head of state, but also as head of government. Also in organizing government institutions the state becomes a barometer in measuring the success of government governance. State apparatus consisting of MPR, DPR, DPD, President, BPK, MA, KY and MK are state institutions whose duties and authorities are regulated in the 1945 Constitution. This article discusses the roles, duties and functions of state institutions, sanctions imposed on deviant state institutions. In this paper deliberately the compilers bring up various supporting theories and examine and discuss the tasks, roles and functions, so that we know that the institutions of this state participate and play a role in advancing the survival of the nation and state.Key words: Function, State Institution, Role, Presidential.